(untitled) (Journal of Preventive and Social Medicine, 2021)
Background: Dental caries is a chronic dental disorder of children and it can result in substantial morbidity due to pain, dysfunction, poor appearance, and problems of speech development. The study was conducted to assess the association between passive smoking and pediatric dental caries. Methods: The cross-sectional study was conducted among 92 school children aged 5-10 years. Data on exposure to passive smoking at both indoor and outdoor were obtained through face to face interview of the parents with the help of semi-structured questionnaire and checklist. Dental caries was diagnosed by clinical examination and passive smoking exposure was assessed by estimated urinary cotinine level. Results: The study revealed that 58.70% children were male and 41% were female respectively. The mean age of the children was 7.20 years. It was found that 59.8% father of the studied children were smoker where 68.5% children reported that some of their family members were indoor smokers. Of all the children, 62% had dental caries and 85.5% of the children had dental caries who were exposed to passive smoking and had significant association between exposure to passive smoking and dental caries (p<0.001). Dental caries was common among children aged 5-6years who were exposed to passive smok ing. The mean urinary cotinine level was 27.81 ng/ml and maximum children (65.2%) had urinary cotinine level more than 10ng/ml who was exposed to passive smoking. The study found significant positive correlation between urinary cotinine concentrations and the duration of exposure to passive smoking (i=0.692, p<0.001). Conclusion: This study suggests reduction of exposure to passive smoking may be an effective measure for prevention of pediatric dental caries. JOPSOM 2020; 39(1): 1-13